DIFFERENCES IN STUDENT CREATIVITY BY APPLYING THE COOPERATIVE LEARNING TYPE TPS AND LEARNING MODEL PBL - Winmery Lasma Habeahan; Muhammad Daut Siagian (Journal Of Educational Experts (JEE), 2021)
The purpose of this study was to see the differences in student creativity by applying 2 learning models, namely the TPS cooperative learning model and the PBL learning model in class VIII of the SMP Swasta Mentari Bangsa Medan. This research is an experimental research. The subjects in this study were all students of class VIII SMP Swasta Mentari Bangsa Medan which consisted of 2 classes. While the object in this study is the creativity of students in the TPS and PBL learning models. This research is supported by several tools such as lesson plans, student activity sheets (LAS), and student handbooks. The instrument used in this study was an essay test of 4 questions that had been tested and declared valid. The average TPS class student pretest was 34,243 while the post-test average was 40,729. PBL class students obtained an average pretest of 35.138 while the average post-test was 46.861. From the calculation results obtained = -3,212 and = 1,996 with dk = 54 and the real level α = 0.05. It can be seen that tcount is not between the interval -1.996 <t <1.996 so that H0 is rejected and Ha is accepted. So from the results of research and hypothesis testing it is concluded that there are significant differences in student creativity by applying the TPS type cooperative learning model and the PBL learning model on cube and block material in class VIII of the SMP Swasta Mentari Bangsa Medan.